Characterization of olive oil from the variety of Lefkoelia Serron of four different times of harvest - Zavala H., Victoria A. (Zamorano: Escuela Agrícola Panamericana, 2025)
The quality of olive oil is not just a matter of geography or processing technique but is also closely related to the specific variety of olive, cultivation practices, and the timing of the harvest. This study evaluated the quality of Lefkoelia Serron olive oil harvested at four different times (pre-mature, mature and post-mature) to see how it aligns with the standards set by the International Olive Council (IOC). Although Lefkoelia Serron has not been studied thoroughly yet, the focus was on understanding how the timing of the harvest influences key quality factors like acid value, oxidative stability, peroxide value, K-values, chlorophyll, carotenoid and phenolic content. The research was designed using a Completely Randomized Design with three replicates, and data was analyzed using ANOVA to identify any significant differences between the samples. The findings revealed that all olive oil samples met the criteria for Extra Virgin Olive Oil (EVOO). However, oils harvested earlier, especially in October, stood out with superior quality traits lower acidity, greater resistance to oxidation, and higher phenolic content compared to those harvested later. This suggests that harvesting olives earlier could be the key to producing high-quality olive oil. To preserve quality and strengthen market position, producers are encouraged to prioritize early harvesting and proper storage methods. Future studies might explore additional factors, such as different environmental conditions and more detailed chemical analyses, to deepen the understanding of what influences olive oil quality.